The Influence of Teacher Professionalism and Student Learning Motivation on Learning Outcomes in Islamic Religious Education at UM Laboratory Junior High School, Malang City - Sumiyati, Sumiyati; Yasin, Ahmad Fatah; Hambali, Muh. (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
Teacher professionalism and student learning motivation are critical factors influencing student achievement, including in the context of Islamic Religious Education (Pendidikan Agama Islam, PAI). This study investigates the extent to which teacher professionalism and student learning motivation affect PAI learning outcomes at the UM Laboratory Junior High School in Malang City, Indonesia. Employing a quantitative correlational research design, the study involved a randomly selected sample of 113 students from grades VII and VIII. Data were collected through structured questionnaires and analyzed using SPSS version 27, incorporating classical assumption testing, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results indicate that teacher professionalism has a statistically significant effect on PAI learning outcomes (p = 0.001), contributing 27.3% to the variance in outcomes. Student learning motivation also showed a significant effect (p = 0.001), with a larger contribution of 54.0%. When analyzed jointly, both variables significantly influenced PAI learning outcomes, with a combined explanatory power of 48.2%. These findings highlight the pivotal role of both teacher competence and student motivation in enhancing the effectiveness of PAI instruction. The study underscores the need for targeted interventions aimed at improving teacher professionalism and fostering student motivation to support more meaningful and successful learning experiences in religious education.